REFORMA SISTEMULUI REZIDENŢIAL DE ÎNGRIJIRE A COPILULUI DIN REPUBLICA MOLDOVA ÎN CONTEXTUL DEZVOLTĂRII ASISTENŢEI SOCIALE PROFESIONISTE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2009)
The reform in residential care system presents a priority in social policy in the field of family and child protection in R. Moldova. Community Social Workers constitutes an essential chain in the process of social policy implementation. They are those, who wife minimal resources ensures the prevention of child separation and abandonment, they achieve the reintegration in the biological/extended family of institutionalization children, they offer support to their families. The article emphasizes the results of reform implementation and describes the system of child protection in R.Moldova. Furthermore, the article chesses the problems and obstacles in the implementation of the reform.